2005
DOI: 10.1016/j.febslet.2005.03.088
|View full text |Cite
|
Sign up to set email alerts
|

A targeted antioxidant reveals the importance of mitochondrial reactive oxygen species in the hypoxic signaling of HIF‐1α

Abstract: Exposure to limiting oxygen in cells and tissues induce the stabilization and transcriptional activation of the hypoxia-inducible factor 1 alpha (HIF-1a) protein, a key regulator of the hypoxic response. Reactive oxygen species (ROS) generation has been implicated in the stabilization of HIF-1a during this response, but this is still a matter of some debate. In this study we utilize a mitochondria-targeted antioxidant, mitoubiquinone (MitoQ), and examine its effects on the hypoxic stabilization of HIF-1a. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 44 publications
3
93
0
2
Order By: Relevance
“…Other studies suggested that cells with impaired mitochondrial function fail to stabilize HIFα under hypoxia, not because of defective ROS-generation, but because of intracellular O 2 re-distribution which leads to increased availability of O 2 as a substrate for the hydroxylation reaction [72,78]. Although these reports challenge a role for mitochondrial ROS in cellular O 2 sensing, they do not explain why antioxidants, including the recently described mitochondrially-targeted compound MitoQ, block hypoxic HIFα activity [79]. In addition, they do not explain why defects which specifically compromise Complex III function prevent hypoxic HIFα activity, while Complex IV defects, that impair cellular respiration and presumably O 2 distribution, leave the hypoxic response intact [28].…”
Section: Role Of Ros In Cellular O 2 Sensingmentioning
confidence: 95%
“…Other studies suggested that cells with impaired mitochondrial function fail to stabilize HIFα under hypoxia, not because of defective ROS-generation, but because of intracellular O 2 re-distribution which leads to increased availability of O 2 as a substrate for the hydroxylation reaction [72,78]. Although these reports challenge a role for mitochondrial ROS in cellular O 2 sensing, they do not explain why antioxidants, including the recently described mitochondrially-targeted compound MitoQ, block hypoxic HIFα activity [79]. In addition, they do not explain why defects which specifically compromise Complex III function prevent hypoxic HIFα activity, while Complex IV defects, that impair cellular respiration and presumably O 2 distribution, leave the hypoxic response intact [28].…”
Section: Role Of Ros In Cellular O 2 Sensingmentioning
confidence: 95%
“…30 The active antioxidant form of MQ is the reduced ubiquinol form, which is regenerated by the electron transport chain, and selectively blocks mitochondrial oxidative damage by detoxifying ROS. 16,17 This and other mitochondrial-targeted antioxidants have been shown to protect this organelle from oxidative stress in isolated cells 32 and living tissues 20 in hypoxia, 26 apoptosis, 29 and cancer. 18 In our experiments, continuous pretreatment with GTN produced a substantial reduction in its vasorelaxant effects of GTN when administered acutely, but not in those of acute DETA-NO.…”
Section: Discussionmentioning
confidence: 99%
“…24 Quantitative assessment of hydrogen peroxide (H 2 O 2 ) was performed with the Amplex Red H 2 O 2 /Peroxidase Assay kit (Molecular Probes, Eugene, Ore). 25,26 GSH content was assessed following incubation (30 minutes) with the fluorescent probe monochlorobimane (MCB) (40ϫ10 Ϫ6 mol/L). GSH levels were also measured by confocal microscopy (Leica, Heidelberg, Germany), following incubation (30 minutes) with 5-chloromethylfluorescein diacetate (CMFDA) (1ϫ10 Ϫ6 mol/L).…”
Section: Measurement Of Ros Production Gsh Content and Complex I Acmentioning
confidence: 99%
“…Preparation of total protein extracts, membrane transfer and detection were carried out as described [22]. Primary antibodies for immunoblot were purchased as follows: Phospo-p38 and p38 from Cell Signaling (Danvers, MA, http://www.cellsignal.com), tubulin and actin from Sigma-Aldrich, and cardiac troponin I from Abcam (Abcam, plc., Cambridge, U.K., http://www.abcam.com).…”
Section: Immunoblotting and Immunocytochemistrymentioning
confidence: 99%
“…Endogenous respiration in whole cells was measured with a Clark-type oxygen electrode (Rank Bros., Bottisham, U.K., http:// www.rankbrothers.co.uk), as described in [22].…”
Section: Cellular Respirationmentioning
confidence: 99%